Kecemasan dan depresi pada pasien gagal ginjal kronis yang menjalani terapi hemodialisis - Caninsti, Riselligia (Konsorsium Psikologi Ilmiah Nusantara, 2013)
Chronic renal disease and hemodialysis therapy were performed 2-3 times a week, have an impact on the patient’s psychological condition. The patient feels frustrated and give up on their life, so that they feel anxiety and depression, they are often able to accept the reality after the person was on the verge of death. In general, patients undergoing treatment in the hospital just to get medical treatment, while the psychological condition which one the reaction of the physical complaints or other factors that are the result of a perceived physical complaints often go unnoticed. This study aims to determine the psychological condition of patients, especially as related to anxiety and depression, through a measurement tool, which can be used by doctors, nurses, psychologists and other health professionals in the hospital setting. Measuring tool used is the Hospital Anxiety and Depression Scale (HADS), which has been designed for use in the hospital setting and is made up of 14 items. The application of HADS to patients, is expected to know the level of anxiety and depression of the patients, so that health care practitioners can provide appropriate treatment to solved patients’ psychological problems. The results showed that 73.33% subjects had relatively normal levels of anxiety, borderline abnormal 23.33%, and 3.33% normal. While the depressed patients in the normal level as much as 76.67%, 23.33% borderline abnormal and no one categorized in abnormal depressed.